Pengaruh mekanisme tata kelola perusahaan terhadap konservatisme akuntansi pada perusahaan terbuka yang terdaftar di Bursa Efek Indonesia - Widijaya Widijaya; Fina Fiorentini (INOVASI, 2021)
This research objective is to investigate the effect of corporate governance mechanisms (managerial ownership, board size, board independence and auditor type) on accounting conservatism of all companies that are listed in Indonesia Stock Exchange (IDX). The method used for this quantitative research to test the relation between corporate governance mechanisms and accounting conservatism is panel data regression by using secondary data from 2016 – 2020 financial report. The amount of samples are 464 companies with 2.320 observations which meet the conditions and criteria. This research shows that managerial ownership has a significant negative effect on conservatism, meanwhile board size, board independence and auditor type have no effect on conservatism. Control variables in this research prove that firm size and sales growth are negatively related to conservatism, while profitability and leverage are positively related to accounting conservatism.